Sistem Monitoring Jentik Nyamuk Di Desa Muktiharjo Berbasis Mobile - Arief Puji Eka Prasetya; Oky Dwi Nurhayati; Kurniawan Teguh Martono (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2016)
High dengue fever cases strongly influenced by the behavior of the public them self. Almost most of the territory in urban and rural areas can be considered as potentially endemic. In the development of the Center of Desease Control give serious action against the locations of the potential for development of the Aedes Aegypti. One way that can be done in order to prevent the environment to being free of dengue wiggler is through some sort of surveys. This monitoring system is designed using Waterfall methodology using the programming language such as Javascript, PHP, CodeIgniter framework, AngularJS, and Ionic also using MySQL database. A needs analysis conducted by interviewing one of the members of Center of Desease Control’s member and the Village Head of Muktiharjo so that the design could be done, appropriate and well targeted. The results of the final project is mobile and desktop applications that can change the performance of the JUMANTIK (Mosquito Eradication Officers) with more modern, neat, and systematic application so that the data obtained can meet the desired needs. The system that has been designed has been tested using black-box method and the results of these tests indicate that all the functions contained in this system has worked well.